Reproductive and metabolic abnormalities in women taking valproate for bipolar disorder: a meta-analysis. (July 2016) - Zhang, Lin; Li, Hua; Li, Shaoping; Zou, Xiaoyi
Abstract: Objective: We aimed to evaluate the relationship between valproate (VPA) and reproductive endocrine abnormalities in women with bipolar disorder. Methods: We searched studies in electronic databases of China Biology Medicine disc, PubMed, and Embase. Two authors collected articles and extracted data independently. Meta-analysis was performed for polycystic ovary syndrome (PCOS) and its components. The mean difference (MD) and 95% confidence interval (CI) were used to compare continuous variables. The Mantel–Haenszel formula was used to calculate the odds ratio (OR). Results: There were statistically significant differences between the VPA treated and non-VPA treated groups in PCOS (OR 6.74; 95% CI 1.66–27.32; P  = 0.00), menstrual disorder (OR 1.81; 95% CI 1.02–3.23; P  = 0.04), and hyperandrogenism (HA) (OR 2.02; 95% CI 1.11–3.65; P  = 0.02). There was no statistically significant difference between the VPA treated and non-VPA treated groups in PCO (OR 1.37; 95% CI 0.71–2.66; P  = 0.35). The overall risk of menstrual disorders, PCO, and HA in the VPA treated group was higher than in the non-VPA treated group (OR 1.75; 95% CI 1.23–2.47; P  = 0.00). The levels of total and free testosterone in the VPA treated group were higher than in the non-VPA treated group (MD 0.12; 95% CI 0.05–0.19; P  = 0.00; MD 0.14, 95% CI 0.07–0.21; P  = 0.00, respectively). Conclusions: VPA was associated with the elevated levels of testosterone and HA in women with BD.